Curcumin Suppresses the Lipid Accumulation and Oxidative Stress Induced by Benzo[a]pyrene Toxicity in HepG2 Cells - Seung-Cheol Lee; Seung-Cheol Jee; Min Kim; Soee Kim; Min Kyoung Shin; Yunkyung Kim; Jung-Suk Sung (MDPI AG, 2021)
Benzo[a]pyrene (B[a]P) is a potentially hepatotoxic group-1 carcinogen taken up by the body through ingestion of daily foods. B[a]P is widely known to cause DNA and protein damages, which are closely related to cell transformation. Accordingly, studies on natural bioactive compounds that attenuate such chemical-induced toxicities have significant impacts on public health. This study aimed to uncover the mechanism of curcumin, the major curcuminoid in turmeric (Curcuma longa), in modulating the lipid accumulation and oxidative stress mediated by B[a]P cytotoxicity in HepG2 cells. Curcumin treatment reduced the B[a]P-induced lipid accumulation and reactive oxygen spicies (ROS) upregulation and recovered the cell viability. Cytochrome P450 family 1 subfamily A polypeptide 1 (CYP1A1) and Cytochrome P450 subfamily B polypeptide 1 (CYP1B1) downregulation resulting from decreased aryl hydrocarbon receptor (AhR) translocation into nuclei attenuated the effects of B[a]P-induced lipid accumulation and repressed cell viability, respectively. Moreover, the curcumin-induced reduction in ROS generation decreased the nuclear translocation of Nuclear factor erythroid-2-related factor 2 (Nrf2) and the expression of phase-II detoxifying enzymes. These results indicate that curcumin suppresses B[a]P-induced lipid accumulation and ROS generation which can potentially induce nonalcoholic fatty liver disease (NAFLD) and can shed a light on the detoxifying effect of curcumin.